PENDAMPINGAN MUJAHADAH DAN ISTIGHOSAH UNTUK MENINGKATKAN KECERDASAN SPIRITUAL KEAGAMAAN SANTRI DAN MASYARAKAT - Choiri, Moh Miftahul; Nurdiansyah, Denny; Rokhim, Auliyaur (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Abstract : This Mujahadah and Istighosah activity was carried out in order to guard and develop the spirituality of the community and students in the Raudhatul Ulum Campurejo Bojonegoro Islamic Boarding School. A person's spiritual level sometimes rises, sometimes falls, so efforts are needed to stabilize this condition. For example, there is a student who has just entered the boarding school and is naughty at first, then after being at the boarding school and graduating, he becomes an obedient child. This cannot be separated from the efforts of a kyai or ustadz, namely dhohir and inner efforts. Dhohir's efforts include teaching, directing, educating and so on. Meanwhile, inner efforts are prayer, penance, mujahadah, istighosah and so on. These two efforts must be carried out in balance. So we, as a community service team, want to hold Mujahadah and Istighosah assistance activities to improve the religious spirituality of the community and students in the Raudhatul Ulum Campurejo Islamic Boarding School, Bojonegoro. The Community Service method used is the Participatory Action Research model. Namely, the mentor goes directly to the field to oversee the mentoring process from the beginning to the end of the activity. The stages or steps that will be taken in carrying out mujahadah and Istighosah assistance to increase religious spiritual intelligence are as follows: Identification of needs and goals, Determining companions, Gathering information, Forming groups or clusters, Preparing programs and schedules, Implementing mujahadah and istighosah practices, Teaching mujahadah and istighosah material, Monitoring and evaluation, Support and motivation and finally program evaluation Keywords: Mujahadah, Istighosah, Spiritual intelligence